If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8-k=-2-6k+6k
We move all terms to the left:
-8-k-(-2-6k+6k)=0
We add all the numbers together, and all the variables
-k-8-(-2)=0
We add all the numbers together, and all the variables
-1k-6=0
We move all terms containing k to the left, all other terms to the right
-k=6
k=6/-1
k=-6
| 1024=4x+2 | | n+285=960 | | s+113=995 | | 2(5x+8)=41+27 | | r+4=-r+10 | | -8y+6(y-2)=-24 | | 10r=-8(-r+1) | | 22=u/19 | | -33=9(3b+4) | | (3x+12)+(2x+42)=180 | | 4x2+10x=x2-x+4 | | n/45=30/125 | | -6a-8(2-16a)=4(19a+19) | | -6g-5g+14=14-11g | | u-70=39 | | 5x-1=-2x-8 | | 2(2x+4)=10x | | p-899=-557 | | 11+5z-20=1+5z | | -2+n/4=0 | | y/5/3+5=25/6 | | p-588=218 | | -6a-8(2-16a)=4(19a+149) | | 18m-12m+16=8m-8 | | 3p-p=14 | | 18d-4+3/8d-4=5 | | 14j=-196 | | -14w+12w-4=14-w | | -40+k=2k | | 3x+15=55-2x | | 45x+60=55x | | -576=16v |